Performance evaluation of a nonlinear Winkler-based shallow foundation model using centrifuge test results. - Raychowdhury, Prishati (Earthquake engineering & structural dynamics.)
When a structure supported on shallow foundations is subjected to inertial loading due to earthquake motions, the foundation may undergo sliding, settling and rocking movements. Even if the capacity of the foundation is mobilized, the soil?foundation interface may dissipate significant amounts of vibrational energy, resulting in reduced force demands to the superstructure. If the capacity is not mobilized, these movements introduce additional flexibility to the system, which may shift its period away from the potentially hazardous zone of response spectra for most earthquake ground motions. In either case, transient and permanent deformations will need to be accounted for. To consider the aforementioned benefits and consequences in performance-based seismic design, robust and reliable numerical modeling tools are needed. In this article, a Winkler-based modeling framework is proposed to address this issue. The model includes a distributed array of mechanistic nonlinear inelastic springs, dashpots, and gap elements, with backbone curves of the nonlinear springs calibrated against shallow foundation experiments. Model evaluation is conducted by simulating the response of a number of centrifuge experiments. Experiments considered include square and strip footings, bridge and building models, static and dynamic loading, footings on sand and clay, a range of static vertical factors of safety, and a range of aspect ratios. It is observed that the model can reasonably predict measured footing response in terms of moment, shear, settlement and rotational demands. In addition, the general hysteresis shape of the moment?rotation, settlement?rotation and shear?sliding curves is reasonably captured.